2016
DOI: 10.1016/j.actatropica.2016.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Wild fauna as a carrier of Salmonella in Reunion Island: Impact on pig farms

Abstract: Salmonellosis is an economic burden to the livestock industry in Reunion Island. In this study, we wanted to improve our understanding of Salmonella epidemiology by studying the wild fauna of Reunion Island. We assessed Salmonella diversity in small non-flying mammals, birds and cockroaches in order to evaluate their potential role in the epidemiology of Salmonella. A total of 268 samples were collected from cockroaches, small mammals and birds. The bacteriological analyses revealed that 11.7% of non-flying ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…It may also carry important protozoa which are mainly dangerous for immune compromised patients [1]. Bacterial pathogens like Salmonella that are important to both humans and livestock have also been isolated from R. rattus in many countries, i.e., Japan, [25], Reunion Island [26], Pakistan [27], and Canada [14]. In the phylogenetic tree it clustered well with the species found in India, Jordan, Tanzania, and other South African studies.…”
Section: Discussionmentioning
confidence: 85%
“…It may also carry important protozoa which are mainly dangerous for immune compromised patients [1]. Bacterial pathogens like Salmonella that are important to both humans and livestock have also been isolated from R. rattus in many countries, i.e., Japan, [25], Reunion Island [26], Pakistan [27], and Canada [14]. In the phylogenetic tree it clustered well with the species found in India, Jordan, Tanzania, and other South African studies.…”
Section: Discussionmentioning
confidence: 85%
“…The research conducted with 62 wild birds, namely 30 Columba livia, 19 Pterodroma baraui, 10 Puffinus lherminieri, and three Phaethon lepturus, from industrial sites and rescue centers, and found that only one specimen of two species each tested positive for Salmonella spp. [31]. The study with 364 Passeriformes and Piciformes found no positive isolate for Salmonella spp.…”
Section: Discussionmentioning
confidence: 92%
“…Given the documented wide host range of S . Typhimurium [ 25 27 ], it was unsurprising that it was a common serotype in all livestock and all associated food commodities. Nevertheless, eggs remain the most commonly implicated food in outbreaks of this serotype [ 2 , 15 ].…”
Section: Discussionmentioning
confidence: 99%